2017
DOI: 10.3389/fpsyg.2017.01115
|View full text |Cite
|
Sign up to set email alerts
|

Leader Humility and Team Innovation: Investigating the Substituting Role of Task Interdependence and the Mediating Role of Team Voice Climate

Abstract: Leadership has been found to be linked with team innovation. Based on social information processing theory and substitutes for leadership theory, this paper examines the influence of leader humility on team innovation. Results from 90 teams showed that leader humility will enhance team innovation by fostering team voice climate. Further, task interdependence substitutes the effect of leader humility on team innovation through an indirect way via team voice climate. This study discussed the theoretical and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 97 publications
1
44
0
Order By: Relevance
“…The leadership literature has provided several theoretical perspectives to explain how leadership influences follower creativity, such as intrinsic motivation and social learning. However, these studies have mainly focused on top-down leadership and the bottom-up aspects of leadership have been largely overlooked (Oc et al, 2015; Wang et al, 2016; Liu et al, 2017). Distinct from top-down leadership, humble leadership is a new type of bottom-up leadership style distinctly characterized by admitting personal limitations, publicly praising followers, and maintaining an open mind (Owens and Hekman, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leadership literature has provided several theoretical perspectives to explain how leadership influences follower creativity, such as intrinsic motivation and social learning. However, these studies have mainly focused on top-down leadership and the bottom-up aspects of leadership have been largely overlooked (Oc et al, 2015; Wang et al, 2016; Liu et al, 2017). Distinct from top-down leadership, humble leadership is a new type of bottom-up leadership style distinctly characterized by admitting personal limitations, publicly praising followers, and maintaining an open mind (Owens and Hekman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Distinct from top-down leadership, humble leadership is a new type of bottom-up leadership style distinctly characterized by admitting personal limitations, publicly praising followers, and maintaining an open mind (Owens and Hekman, 2012). Although early propositions have pointed to the importance of leader humility within organizations, studies toward exploring the influence of humble leadership on followers – and the underlying mechanisms involved – have only recently begun to attract attention (e.g., Jeung and Yoon, 2016; Wang et al, 2016; Liu et al, 2017; Ou et al, 2017, 2018; Rego et al, 2017; Yuan et al, 2018). Furthermore, these studies are primarily limited to the individual-level or team-level analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar vein, Rego et al (2017b) also pointed out that humble leadership can increase team performance via enhanced collective humility and team psychological capital (sequential mediation). Liu et al (2017) demonstrated that humble leadership can facilitate team innovation by shaping the team voice climate. Chen et al (2018) identified a moderated mediation connection between humble leadership, identification with the leader, psychological empowerment, and employee proactive behavior.…”
Section: Humble Leadership and Ocbmentioning
confidence: 99%
“…For organizations or team, voice taking will promote team learning and team innovation, reduce turnover, and increase organizational effectiveness (Chen & Hou, 2016). Previous research found that voice taking is beneficial to improving decision accuracy (LePine & VanDyne, 1998), team performance (Frazier & Bowler, 2015;Liu et al, 2017).…”
Section: Consequence Variablementioning
confidence: 99%